Ion motion in a magnetized electron gas considered as the scattering in a deformed Coulomb potential - Novak, O.P. (Reports of the National Academy of Sciences of Ukraine, 2016)
The energy losses of an ion moving in a magnetized electron gas have been studied. The transverse motion of electrons is assumed to be completely suppressed by the field. It is shown that the problem can be reduced to the motion of a single particle in an anisotropic potential. The oscillations of the scattered particle and the transferred energy are found in the region of small impact parameters.